The Role of Private Schools in Education Reform in Nigeria - Nwaelele Okezie; Jumbon Mercy Tamuno (International Journal on Integrated Education, 2022)
The broad intent of any educational reform is premised on the assumption that it is capable of improving educational process and practices, hence, the need for evaluation of the system’s process in order to determine the efficiency and effectiveness of resource allocation. Education is capital intensive in terms of human, financial and material resources. Its provision and management determine the quality and functionality of the system. This paper sought to assess the extent to which privatization policy has actually addressed quality improvement and also verify if there is justification for private participation in the provision and management of tertiary institutions in Nigeria in an attempt to suggesting some quality improvement strategies. The rationale for deregulation and privatization of the sector was provided and the challenges in the policy were also highlighted. Based on this, it was concluded that though privatization policy enhances access, it is not a panacea to quality tertiary education. In addition, there must be a strict adherence to globally set criteria for improvement, enhancement of educational agencies, especially those in charge of management and supervision of tertiary institutions as well as regular reforms in the process and practice within the sector.